THE TRANSFORMATION OF ISLAMIC VALUES-BASED EDUCATION MANAGEMENT: A CRITICAL ANALYSIS OF THE IMPLEMENTATION OF THE MERDEKA CURRICULUM AND THE ISLAMIC LEADERSHIP PARADIGM IN EDUCATIONAL INSTITUTIONS - Syaiful Bahri Djamarah; Suhana binti Sarkawi (CV. Adiba Aisha Amira, 2025)
The transformation of Islamic values-based education management is a strategic step in strengthening the direction of national education to be in line with the spiritual and moral goals of the nation. This study aims to critically analyse how the implementation of the Merdeka Curriculum can be integrated with the principles of Islamic education management, as well as how the Islamic leadership paradigm plays a role in the transformation process. Through library research, this study examines various scientific sources in the form of books, journals, and official documents relevant to the theme of Islamic education management and the Merdeka Curriculum policy. The results of the study show that the Merdeka Curriculum, with its principles of flexibility and independence, is in line with Islamic values such as tauhid, amanah, adil, and ihsan, which emphasise a balance between intellectual and moral intelligence. Meanwhile, the Islamic leadership paradigm based on the values of shiddiq, amanah, tabligh, and fathanah is an important factor in directing the transformation of education management to be character-building, visionary, and oriented towards the benefit of the people. The synergy between the Merdeka Curriculum and Islamic leadership produces a holistic, competitive, and spirituality-based educational management model, capable of producing a generation that is knowledgeable, moral, and adaptive to the developments of the times.